Generative Anthropology’s Overcoming of Metaphysics - Gans, Eric Lawrence (2024)
At least since Hegel’s attempt at the dialectical fusion of philosophy with the totality of human history, Western thinkers have felt the urgency of escaping the realm of metaphysics inaugurated by Parmenides and Plato. By extending the world of Ideas to include all dimensions of human activity from the esthetic and religious to the political,...